AUTOCLAVE FOR MODERN BUILDING MATERIALS WORKING IN THE METHOD - Kurbanov A. T. (American Journals, 2023)
For the fast and high-quality production of modern construction materials, it is necessary to use different heat treatment devices for various structural elements, because they are required to serve for a long time without losing their strength under the influence of external forces. The article presents calculations on the methods of heat treatment of building materials by the autoclave method.
Keywords: avnoclave, structure, operation, constructive calculation, heat calculation, heat consumption, lost heat, heat balance.